2007
DOI: 10.1165/rcmb.2006-0386oc
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Adult Mouse Lung Mesenchymal Progenitor Cell Population

Abstract: Contained within the adult lung are differentiated mesenchymal cell types (cartilage, smooth muscle, and myofibrobasts) that provide structural support for airways and vessels. Alterations in the number and phenotype of these cells figure prominently in the pathogenesis of a variety of lung diseases. While these cells are thought to arise locally, progenitors have yet to be purified. In previous work, we developed a method for isolating progenitors from lung tissue: this technique takes advantage of the unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 38 publications
(36 reference statements)
6
99
0
1
Order By: Relevance
“…2F). Previous work by other investigators has demonstrated that lung SP cells from adult mice are composed of CD45 þ and CD45 À SP cells (26).…”
Section: Cd45mentioning
confidence: 90%
“…2F). Previous work by other investigators has demonstrated that lung SP cells from adult mice are composed of CD45 þ and CD45 À SP cells (26).…”
Section: Cd45mentioning
confidence: 90%
“…In a large-animal model of experimental emphysema, the lung-derived mesenchymal cell recently described by Karoubi et al and others (2,16,27,36). These cells evidence of tissue regeneration with increased blood perfusion and extracellular matrix (ECM) content was display regenerative capacity through expression of basement membrane proteins and growth factors.…”
Section: Paracrine Effects Of Lmscs On Epithelial Cellsmentioning
confidence: 99%
“…Even with priming, only low-level BM-MSC retention has been observed in vivo (18,20). Furtherhave been isolated from various adult tissues including adipose, liver, lung, and heart, most studies evaluating more, therapeutic responses to BM-MSC transplantation have been limited to animal models of inflammatory their regenerative capacity have utilized bone marrowderived cells (17,25,29,33,36,40). Several lines of evilung diseases, such as asthma and acute lung injury (21,30,42).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of lung MSC to differentiate into traditional mesenchymal lineages of osteoblast, adipocyte and chondrocyte and their cell surface expression of accepted mesenchymal markers is evaluated for each cell preparation. Cytogenetic banding analysis is also performed to confirm the absence of gross chromosomal abnormalities 2,3,[8][9][10][11] . …”
Section: Isolation Culture and Characterization Of Lung Msc And Clonesmentioning
confidence: 99%